Crustal thickness variations and seismicity of northwestern south america (2007)
Any uncompensated mass of the northern Andes Mountains is presumably under pressure to adjust within the Earth to its ideal state of isostatic equilibrium. Isostasy is the ideal state that anyuncompensated mass seeks to achieve in time. These pressures interact with the relative motions between adjacent plates that give rise to earthquakes along the plate boundaries. By combining thegravity MOHO estimates and crustal discontinuities with historical and instrumental seismological catalogs the correlation between isostatically disturbed terrains and seismicity has been established.The thinner and thicker crustal regions were mapped from the zero horizontal curvature of the crustal thickness estimates. These boundaries or edges of crustal thickness variations were compared tocrustal discontinuities inferred from gravity and magnetic anomalies and the patterns of seismicity that have been catalogued for the last 363 years. The seismicity is very intense along the Nazca-NorthAndes, Caribbean-North American and North Andes-South American collision zones and associated with regional tectonic compressional stresses that have locally increased and/or diminished bycompressional and tensional stress, respectively, due to crustal thickness variations. High seismicity is also associated with the Nazca-Cocos diverging plate boundary whereas low seismicity is associated with the Panama-Nazca Transform Fault and the South American Plate.